Leiomyosarcomna Presenting as Abdominal Pain in a 50 Years Old Woman: A Case Report (Anwer Khan Modern Medical College Journal, 2011)
Leiomyosarcoma of uterus is a comparatively rare tumor we come across in daily histopathological examination. Clinical presentation of a leiomyosarcoma is varied and includes dysfunctional uterine bleeding, abdominal distention, abdominal pain and metastatic symptoms depending on the organ involved like Lung, bone and brain. Here we report a case of leiomyosarcoma in a 50 year old woman having a single complain of persistent abdominal pain for last 1 year or so. Clinically and by ultrasonogram it was diagnosed as a case of large fibroid. Subsequent histopathological diagnosis was leiomyisarina. Any post menopausal woman having persistent abdominal pain and a clinical and USG diagnosis of fibroid a differential of leiomyosarcoma should be borne in mind of the physicians. Key Words: Leiomyosarcoma; Abdominal Pain DOI: 10.3329/akmmcj.v2i1.7469 Anwer Khan Modern Medical College Journal 2011; 2(1): 32-35